2021
DOI: 10.1371/journal.pone.0256857
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mortality with regard to healthcare services availability, health risks, and socio-spatial factors at department level in France: A spatial cross-sectional analysis

Abstract: Background The 2019 coronavirus (COVID-19) epidemic began in Wuhan, China in December 2019 and quickly spread to the rest of the world. This study aimed to analyse the associations between the COVID-19 mortality rate in hospitals, the availability of health services, and socio-spatial and health risk factors at department level. Methods and findings This spatial cross-sectional study used cumulative mortality data due to the COVID-19 pandemic in hospitals until 30 November 2020 as a main outcome, across 96 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 28 publications
2
21
2
Order By: Relevance
“…found the absence of correlation between mortality rate with doctor to population ratio during the first six months of the epidemic [33], our district-level analysis found that a higher COVID-19 mortality rate was strongly associated with a lower number of doctors per 100,000 population at district-level. This finding contrasts a previous finding from a higher-income country, reporting an association between higher COVID-19 mortality rate with higher physicians density in France [34].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…found the absence of correlation between mortality rate with doctor to population ratio during the first six months of the epidemic [33], our district-level analysis found that a higher COVID-19 mortality rate was strongly associated with a lower number of doctors per 100,000 population at district-level. This finding contrasts a previous finding from a higher-income country, reporting an association between higher COVID-19 mortality rate with higher physicians density in France [34].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to a previous province-level analysis (n=34) found the absence of correlation between mortality rate with doctor to population ratio during the first six months of the epidemic [33], our district-level analysis found that a higher COVID-19 mortality rate was strongly associated with a lower number of doctors per 100,000 population at district-level. This finding contrasts a previous finding from a higher-income country, reporting an association between higher COVID-19 mortality rate with higher physicians density in France [34]. In Indonesia, the lack of doctors, combined with the high number of infections [35] and deaths among health care workers and doctors [36], especially during the early phase of the epidemic, had weakened the health system resilience.…”
Section: Discussionmentioning
confidence: 60%
“… [23] and Tchicaya and coll. [24] focused on COVID-19, finding a negative association between the availability of medical personnel and mortality in Hubei province in China and France, respectively. It is worth noting that the density of doctors indicator includes both practising and non-practising physicians who were registered and entitled to practise as healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 also shares structural and phylogenetic analogy with the Middle East Respiratory Syndrome Coronavirus (MERS-CoV) emerged in 2012. Differently from its predecessors, SARS-CoV-2 has a lower mortality ratio (estimated at around 2-3 %) [6][7][8] and in some cases it develops asymptomatically, especially for its latest B.1.1.519 (omicron) variant. [9][10][11] However, its high contagiousness and the possible development of severe outcomes, especially in elder patients or subjects presenting comorbidities, has caused and still causes an impressive stress on the health systems, only mitigated by the development of novel vaccines also including the messenger RNA (mRNA) strategy.…”
Section: Introductionmentioning
confidence: 94%